2009
DOI: 10.1080/01674820802545818
|View full text |Cite
|
Sign up to set email alerts
|

One year follow-up of post-partum-onset depression: the role of depressive symptom severity and personality disorders

Abstract: This study suggests that women with PPD, scoring high in the EPDS scale 6 weeks post-partum and having a personality disorder, run a higher risk for depression at 1-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Rates of depression and anxiety were elevated in women with PCOS (33.1% and 21.4%, vs. 17.0% and 10.6% in controls, respectively). Other studies have found similar associations between PCOS and depression and anxiety 62 65 , and report that 40% of women with PCOS experienced clinical depression 64 , and 34% of women with PCOS were diagnosed with anxiety 62 . Our observed prevalence was higher than that found in the Swedish population (16.4% vs. 11.1% in PCOS cases vs. controls) 31 .…”
Section: Discussionmentioning
confidence: 58%
“…Rates of depression and anxiety were elevated in women with PCOS (33.1% and 21.4%, vs. 17.0% and 10.6% in controls, respectively). Other studies have found similar associations between PCOS and depression and anxiety 62 65 , and report that 40% of women with PCOS experienced clinical depression 64 , and 34% of women with PCOS were diagnosed with anxiety 62 . Our observed prevalence was higher than that found in the Swedish population (16.4% vs. 11.1% in PCOS cases vs. controls) 31 .…”
Section: Discussionmentioning
confidence: 58%
“…Our findings agree with data from previous research concerning the personality organization as a factor of vulnerability in perinatal depression, which had found two different premorbid personalities at the basis of perinatal depression, using different assessment tools. Some research has identified a specific bond between obsessive-compulsive or dependent personality traits and depressive perinatal risk [ 10 , 12 14 ]. Vulnerability elements were linked to feelings of guilt and inadequacy, low self-esteem, and scarce autonomy, in association with rumination, lack of assertiveness, and hypersensitivity toward refusal.…”
Section: Resultsmentioning
confidence: 99%
“…The tendency of these mothers to experience a state of growing anxiety, along with a predisposition to face intimate relationships with an attitude of hyperresponsibility, can transform the engagement in child care into an emotional burden that can overwhelm these patients, leading to a depressive condition. Akman et al noticed that women with an avoidant, dependent, or obsessive-compulsive personality disease had greater chances of postpartum depressive onset [ 10 ]; Uguz et al highlighted that the most significant signs during the first year after giving birth were higher scores on the Edinburgh Postnatal Depression Scale (EPDS) and the existence of a personality disorder, particularly obsessive-compulsive and dependent disorders [ 12 ]. Further research linked the fear of relationships (typical of a C-cluster personality disorder) with postnatal depression symptoms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of 34 women with depressive symptoms assessed with the EPDS at six weeks and one year post partum, those with postpartum depression persisting at one year (EPDS score >12) were significantly more likely to have an axis II disorder (odds ratio 21.1, 1.49 to 2.47; P=0.02) 100. Mothers with strong borderline and narcissistic traits or disorders often have difficulty with effective parenting, and studies suggest that their dysregulation of affect and difficulty with empathy and mentalizing may all have negative effects on child development 101.…”
Section: Personalized Treatment For Specific Clinical Characteristicsmentioning
confidence: 99%